Analisis Studi Kelayakan Bisnis Pada Usaha Bobilu Bola-Bola Ubi Lumer - Dewi, Rosiana; Saepuloh, Asep; Perwito, Perwito (LANCAH: Jurnal Inovasi dan Tren, 2025)
This research aims to analyze whether the Bobilu Bola-Bola Ubi Lumer business is feasible or not to be developed. Business feasibility studies provide benefits for measuring and knowing whether a business is feasible or not. Business feasibility studies really help business people to know whether the business they are running is successful or profitable. The research method used is a qualitative approach with descriptive methods, data collected comes from scientific journals and websites. The analysis focuses on 5 (five) aspects of the business feasibility study, namely market and marketing aspects, technical/operational aspects, management/organizational aspects, financial aspects, and environmental impact aspects. The research results show that the Bobilu Bola-Bola Lumer Yam business has good profit potential with low production costs and stable market demand. By using the Net Present Value (NPV), Payback Period (PP), Profitability Index (PI) and Internal Rate of Return (IRR) methods, the Lumbered Sweet Potato Balls business was declared feasible to run.